Memorandum on times of waking patients in hospitals - Hastings, Somerville, 1878-1967 (1931)
1931 1931 1930s 2 pages -2- The real reason why hospital authorities are unwilling to change the time-honoured custom of early waking, is because they fear that an increase of nursing staff will be rendered necessary. Where the provision of nurses is anything like adequate however, the hour of waking patient's can be changed to 7 a.m. without any increase of staff and has been in certain cases. The most obvious disadvantage of this system is that doctors and students do not normally enter the ward before 10 a.m. and if there is much to do this may be rather late. In practice, however, it is often found possible to admit them to part of a ward before this hour. Another alleged disadvantage is that patients are not washed before having their breakfast. But they are not washed before their other meals. In addition to the increased comfort of the patients and the medical value of the possibility of longer sleep, there is under the old system, a wait before breakfast of rarely less than two hours in the case of those washed first. More important is the fact that under the new system, patients are washed by dar [day] nurses who are fresh on duty, instead of by tired nurses who have been up all night. They are washed also under the direct supervision of the Ward Sister who comes on duty at 7.30. or 8.a.m. Thus the most important work of the day from the nurses' point of view, is carried out carefully and under adequate supervision, and except in mid-winter by daylight. Consequently symptoms, such as rashes, colour of skin, etc., can be more readily observed At one infirmary the patients are given a cup of tea at 6 a.m. and their sanitary needs are attended to, but washing and bedmaking does not commence till 7 a.m. and breakfast does not start till 8.30. At another, the following time-table was introduced a year ago and has been found to work satisfactorily. During the night Night Nurses do as much of the extra work as possible to relieve the Day Nurses - Clean slabbs, prepare dressing trolleys, etc. 6 a.m. Only 4 hourly treatment and 4 hourly charts to be done. 6.30 a.m. Women's Ward - Sanitary round and backs of helpless patients done, and mouth washes given. Sanitary utensils collected. No patient to be awakened before breakfast except for treatment ordered and necessary sanitary requirements. 7.0 a.m. Lights on and breakfast. 7.20.a.m. Clear away breakfast and give out bowls for patients who wash themselves. 7.25 a.m. Day nurses come on duty and do all washings, charts, etc., (the patient is attended to, washed, bed made, etc., at one time). 8.a.m. Night nurses report and go off duty. 10.0 a.m. Ward tidy and open to House Officers, etc. 292/842/1/6